Need Identification on Android-Based Neighborhood Electric Vehicle Dashboard View Using The Kano Model - Fajar, Nurhikmah; Wibisono, Muh Arif; Kusuma, Enas Dhuhri (TALENTA Publisher, 2021)
A customer is someone who repeatedly comes to the same place when he wants to buy an item or get service because he is satisfied with the goods or services. Companies must understand the needs and desires of customers in order to satisfy customer needs. Technology that is currently developing is electric cars, especially the Neighborhood Electric Vehicle (NEV) with the application of smartphones. Conventional dashboards can be replaced with smartphones Android-based. Fulfillment of customer satisfaction with smartphone dashboard products is identified by conducting a customer desires survey and categorized it using the Kano model. The survey was conducted on 14 attributes by producing three categories, such as one dimensional, attractive and indifferent. The Android dashboard is built based on survey results instruments. The use of Arduino nano and ESP32 as controllers that process vehicle instrument data sent using Wi-Fi in real time to Android-based smartphones has a maximum error of 5% for speed data.